Effects of introducing MEWS on nursing staff in mental health inpatient settings. Issue 2 (March 2014) - Shaddel, Farshad; Khosla, Vivek; Banerjee, Subimal
Abstract The Modified Early Warning Score (MEWS) is now commonly used in the assessment of physically unwell patients in non‐acute hospital wards. The effect of the introduction of MEWS on the confidence of inpatient psychiatric nurses in identifying the severity of a physically deteriorating patient, and taking appropriate clinical action, has not been reported previously. The authors undertook a cross sectional survey looking at the level of confidence of qualified mental health nurses, and their ability to make correct clinical decisions, before and after introduction of the MEWS tool. Copyright © 2014 John Wiley & Sons